Social Disconnection During COVID‐19: The Role of Attachment, Fear of Missing Out, and Smartphone Use. (26th August 2021) - Parent, Natasha; Dadgar, Kyle; Xiao, Bowen; Hesse, Cassandra; Shapka, Jennifer D.
Abstract : This mixed‐methods study explored adolescents' ( n  = 682) feelings of social connection in the time of the COVID‐19 pandemic and examined potential risk (fear of missing out, problematic smartphone use) and protective (parent/peer attachment, smartphone use) factors to social disconnection. Data were collected from two schools in Canada using an online survey with questionnaires and open‐ended questions. Three themes regarding adolescents' feelings of social connection during the pandemic were identified through thematic content analysis: (1) feeling socially connected, (2) feeling socially disconnected, and (3) feeling socially indifferent. Moreover, regression analysis identified secure peer attachments as a protective factor against social disconnection in the time of the COVID‐19 pandemic, while fear of missing out was identified as an independent risk factor.